Analysis of the Influence of Brand Image, Price, and Digital Marketing on Purchasing Decisions in Tea Break Consumer - Meriska, Idzza Hayu; Sukaris, Sukaris (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this research is to understand the extent of the impact of brand image, price and digital marketing on purchasing decisions for Tea Break customers. This research was carried out using quantitative research methods which can be interpreted as methods used to research certain populations or samples, collecting data using techniques such as observation, interviews, questionnaires, along with literature and literature reviews to test the hypotheses that have been established. The sample in this research was 168 Tea Break consumers. The sampling technique is accidental sampling. The results of this research show that brand image and digital marketing influence purchasing decisions, while price does not influence Tea Break purchasing decisions.